EFFECTIVE CONTROL SYSTEM OF THE INTEGRATED INDUSTRIAL COMPANY - K. A. Dyundik (Модернизация, инновация, развитие, 2016)
In article the organizational and administrative structure of the integrated metallurgical company is investigated. It is shown that linearly – a staff control system to become a limiting factor in its development. Management of transformations represents purposeful translation process of the integrated metallurgical company in a new qualitative state. The purpose . The subject of the article is to analyze the organization of management, to improve it on the basis of a new conceptual approach to the modernization of the control system integrated steel companies and the allocation of the subsystems.Methodology. The methodological basis of this article are the comparative analysis methods.The Results. Studied approaches to the development of integrated management of the metallurgical company, the possibility of change.Conclusions / signifi cance. Management development in an integrated steel company requires in-depth study of existing internal operating conditions and specifi cs of the company, as well as the planning and implementation of measures to improve its receptivity to innovation.